2018
DOI: 10.1108/hff-01-2018-0009
|View full text |Cite
|
Sign up to set email alerts
|

Stagnation-point flow of an aqueous titania-copper hybrid nanofluid toward a wavy cylinder

Abstract: Purpose The purpose of this paper is to investigate analytically the steady general three-dimensional stagnation-point flow of an aqueous titania-copper hybrid nanofluid past a circular cylinder that has a sinusoidal radius variation. Design/methodology/approach First, the analytic modeling of hybrid nanofluid is presented, and using appropriate similarity variables, the governing equations are transformed into nonlinear ordinary differential equations in the dimensionless stream function, which is solved by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
91
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 147 publications
(91 citation statements)
references
References 55 publications
(67 reference statements)
0
91
0
Order By: Relevance
“…In the present model, 0.1 volume fraction of silica (ϕ 1 ) is included to the host liquid (H 2 O) and accordingly molybdenum disulphide (ϕ 2 ) is introduced with numerous concentrations to obtain MoS 2 -SiO 2 /water hybrid nanosuspension. By considering the different combination of nanoparticles, the similar approach has been investigated by many researchers [46,49,50]. The surface roughness is modeled in terms of large frequency and low amplitude sinusoidal waves.…”
Section: Resultsmentioning
confidence: 99%
“…In the present model, 0.1 volume fraction of silica (ϕ 1 ) is included to the host liquid (H 2 O) and accordingly molybdenum disulphide (ϕ 2 ) is introduced with numerous concentrations to obtain MoS 2 -SiO 2 /water hybrid nanosuspension. By considering the different combination of nanoparticles, the similar approach has been investigated by many researchers [46,49,50]. The surface roughness is modeled in terms of large frequency and low amplitude sinusoidal waves.…”
Section: Resultsmentioning
confidence: 99%
“…[24–33] examined the hybrid nanofluid flow's dual solutions. Similar problems were continuously studied by several researchers [34–43] with various physical conditions. Additionally, nanofluid [44–46] and hybrid nanofluid [47–52] review papers can be found in the literature for further reading.…”
Section: Introductionmentioning
confidence: 97%
“…Hayat et al 14 inspected the rotating flow problem of hybrid nanofluids. The aqueous Titania-copper hybrid nanofluid stagnation point flow towards the stretching tube was explored by Yousefi et al 15 . Subhani and Nadeem 16 studied the behavior of (hybrid nanofluid) over the stretching surface.…”
Section: Introductionmentioning
confidence: 99%